Los excesos del mono: salvajismo, transgresión y deshumanización en el pensamiento nahua del siglo xvi - Jaime Echeverría García (Journal de la Société des Américanistes)
Of the many symbolisms attributed to the monkey among the ancient Nahuas those related to excess and transgression stand out, as these qualities characterize for the most part the essence of this mammal. For the sixteenth century Nahuas, excessive behavior threatened the human identity, resulting in a symbolic dehumanization. Nonetheless, in mythical narratives, the mutation into an animal would usually actually happen. In addition to the symbolisms already mentioned, monkeys also represented the savage state of man, which can be understood in two ways: 1. as the state of degeneration of a human being caused by his shortcomings; 2. as a primary savage state that every man must undergo in order to reach culture.